Planting the Seeds: Orchestral Music Education as a Context for Fostering Growth Mindsets - Holochwost, Steven J.; Bose, Judith Hill; Stuk, Elizabeth; Brown, Eleanor D.; Anderson, Kate E.; Wolf, Dennie Palmer (Frontiers in Psychology, 2021)
Growth mindset is an important aspect of children’s socioemotional development, and is subject to change due to environmental influence. Orchestral music education may function as a fertile context in which to promote growth mindset; however, this education is not widely available to children facing economic hardship. This study examined whether participation in a program of orchestral music education was associated with higher levels of overall growth mindset and greater change in levels of musical growth mindset among children placed at risk by poverty. After two years of orchestral participation, students reported significantly higher levels of overall growth mindset than their peers; participating students also reported statistically-significant increases in musical growth mindset regardless of the number of years they were enrolled. These findings have implications for future research into specific pedagogical practices that may promote growth mindset in the context of orchestral music education, and more generally for future studies of the extra-musical benefits of high-quality music education.